The Gospels : a new translation - Ruden, Sarah (Modern Library, 2021)
"Destined to become a definitive edition, an eminently readable new translation of the Gospels from one of today's most respected exponents of ancient literature, allowing readers from all walks of life to appreciate these important texts with fresh eyes and renewed understanding. In this remarkable new translation of the Gospels, Sarah Ruden treats the books of Mark, Matthew, Luke, and John with unprecedented precision, uniquely concentrating on the original words and sensitively reflecting on their historical and literary context, to give us the most accessible version of the text available to date. Stripping away the accretions of later theology and pedantry that cover standard English editions of the Bible, this masterful translation presents each Gospel as a narrative that can be read clear through and understood on its own terms. In her skillful and illuminating introduction, Ruden explains where the Gospels came from, how their forms evolved, and how they set about revolutionizing world thought. Succinct yet illuminating footnotes and a discursive glossary explain the many word choices that depart from the traditional ones. The result is a striking and persuasive reappraisal of the "good news" of the Gospels. An extraordinary feat of scholarship and understanding, Sarah Ruden's welcoming new translation is a ground on which a great variety of readers can meet, forming the basis for new debate, discussion, and inspiration for years to come"--